The impact of CSR activities on trust: the role of perceived brand authenticity and brand personality - Rodrigues, Ana Rita Cardoso Ferreira (2018)
This work studies how the impacts of CSR on trust depend on a brand’s personality, while analysing if they are driven by changes in perception of brand authenticity. An experiment was undertaken in which respondents were subject to one of four scenarios which varied in terms of the personality and the existence (or not) of CSR, being then enquired about authenticity and trust. Results demonstrated a significant effect of personality on authenticity and trust, while CSR only affected significantly authenticity. Authenticity was shown to mediate the effect of CSR on trust, indicating the existence of a suppressor variable.